EDITORIAL General Notions About the Integrated Computer System for Researching Biomotrocity Parameters at the Young Population from Romania – Biomotric - NISR (Arena-Journal of Physical Activities, 2021)
National Institute for Sport Research, Bucharest Corespondence: NISR (e-mail: office@sportscience.ro)